Identifying evolving priorities in national river governance from Parliamentary Questions. Issue 9 (2nd September 2022) - Azhoni, Adani; Holman, Ian; Grabowski, Robert C.
Abstract: Rivers and their surrounding land provide resources and services that result in trade-offs requiring legislative and institutional interventions, for which the perspectives of law-policymakers and their societal values and political expediencies play a major role in decision-making. This study critically evaluates the evolving land–river governance in large democratically elected governments with complex developmental priorities and how law-policymakers' recognition of emerging issues of river management influences common pool environmental resources governance. We selected an emerging economy – India – and analysed Parliamentary Questions (PQs) between 1999 and 2020 using a mixed method approach. Conflicting priorities over economic development, pollution management, socio-cultural values and inter-state–centre issues shape the evolving priorities of land–river governance. A declining focus on large-scale dams coupled with increasing attention on inter-basin water transfers, river conservation and pollution abatement, demonstrates an evolution away from the earlier narrow view of rivers for irrigation and hydropower. Our analysis demonstrates how the priorities of law-policymakers and political expedience play a critical role in river governance and thereby provide important insights into common pool environmental resources governance for sustainable development while also identifying important knowledge gaps and suggesting scopes for interdisciplinary studies. HIGHLIGHTS: Analysed Indian Parliamentary Questions concerning rivers over two decades. Evolving societal values, priorities and political pressures represented. Declining focus on dams and large-scale reservoirs; indicating a shift from an earlier era of viewing rivers narrowly for irrigation and hydropower. Indian Parliamentarians are paying increasing attention to inter-basin water transfers, river conservation and pollution. Graphical Abstract